LINGUISTIC SPIRITUALITY: THE INTERSECTION OF KAWI LANGUAGE AND HINDU RELIGIOUS EXPRESSION - I Wayan Mandra; I Wayan Artayasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study investigates the intricate relationship between language and spirituality through an in-depth analysis of the Kawi language and its role in Hindu religious expression, particularly within the Indonesian context. As an ancient literary and liturgical language, Kawi functions not merely as a communicative tool, but as a complex symbolic system that encodes theological doctrines, philosophical insights, and ritual meanings. Its continued use in sacred texts, mantras, and ceremonial performances reflects a dynamic interaction between linguistic form and spiritual experience. Employing a qualitative interdisciplinary approach, this research integrates philological analysis, hermeneutic interpretation, semiotic examination, and anthropological observation to explore how Kawi operates across textual, ritual, and social dimensions. The study examines not only the structure and meaning of Kawi texts, but also their lived significance in religious practice, including how practitioners interpret, internalize, and transmit spiritual knowledge through language. The findings demonstrate that Kawi serves as a vital bridge between the material and spiritual realms, enabling the articulation of metaphysical concepts that are often beyond the reach of everyday language. It shapes religious consciousness by structuring how devotees understand cosmology, ethics, and the nature of divinity. Furthermore, Kawi plays a crucial role in preserving sacred knowledge and sustaining cultural identity, particularly in the face of modernization and linguistic shift. This research contributes to broader discussions on linguistic spirituality by highlighting the enduring relevance of sacred languages in contemporary religious life. It underscores the need for preservation efforts, not only as a matter of cultural heritage, but also as a means of maintaining spiritual continuity and depth within religious communities.